Comprehensive Assessment of Coronary Plaque Progression With Advanced Intravascular Imaging, Physiological Measures, and Wall Shear Stress: A Pilot Double‐Blinded Randomized Controlled Clinical Trial of Nebivolol Versus Atenolol in Nonobstructive Coronary Artery Disease. Issue 1 (January 2016) - Hung, Olivia Y.; Molony, David; Corban, Michel T.; Rasoul‐Arzrumly, Emad; Maynard, Charles; Eshtehardi, Parham; Dhawan, Saurabh; Timmins, Lucas H.; Piccinelli, Marina; Ahn, Sung Gyun; Gogas, Bill D.; McDaniel, Michael C.; et al.
Abstract : Background: We hypothesized that nebivolol, a β‐blocker with nitric oxide–mediated activity, compared with atenolol, a β‐blocker without such activity, would decrease oxidative stress and improve the effects of endothelial dysfunction and wall shear stress (WSS), thereby reducing atherosclerosis progression and vulnerability in patients with nonobstructive coronary artery disease. Methods and Results: In this pilot double‐blinded randomized controlled trial, 24 patients treated for 1 year with nebivolol 10 mg versus atenolol 100 mg plus standard medical therapy underwent baseline and follow‐up coronary angiography with assessments of inflammatory and oxidative stress biomarkers, microvascular function, endothelial function, and virtual histology intravascular ultrasound. WSS was calculated from computational fluid dynamics. Virtual histology intravascular ultrasound segments were assessed for vessel volumetrics and remodeling. There was a trend toward more low‐WSS segments in the nebivolol cohort ( P =0.06). Low‐WSS regions were associated with greater plaque progression ( P <0.0001) and constrictive remodeling ( P =0.04); conversely, high‐WSS segments demonstrated plaque regression and excessive expansive remodeling. Nebivolol patients had decreased lumen and vessel areas along with increased plaque area, resulting in more constrictive remodeling ( P =0.002). There were no significant differences in biomarker levels, microvascular function, endothelial function, or number of thin‐capped fibroatheromas per vessel. Importantly, after adjusting for β‐blocker, low‐WSS segments remained significantly associated with lumen loss and plaque progression. Conclusion: Nebivolol, compared with atenolol, was associated with greater plaque progression and constrictive remodeling, likely driven by more low‐WSS segments in the nebivolol arm. Both β‐blockers had similar effects on oxidative stress, microvascular function, and endothelial function. Clinical Trial Registration: URL:https://clinicaltrials.gov/ . Unique identifier: NCT01230892.